Explorer l’activité de diagnostic d’une parcelle forestière par des apprenants forestiers pour favoriser l’apprentissage de gestion de situations dynamiques en lien avec le vivant - Thibault Chiron; Dominique Guidoni-Stoltz; Patrick Mayen (Recherches en Éducation)
From a vocational didactic point of view, we are interested in activity of forest plot diagnostic when it carried out by forest’s professional learners. We analyse their reasoning that they leat to decide silviculture actions. This diagnostic activity is complex, insofar as they work in dynamic, life-related work situations. They must identify the processus of forest’s evolution, its dynamic, and then must detect the consequences of their action in the long term. From a thematic analysis of learners' discourse, we rely on the concept of scheme described by Vergnaud to characterize the activity of diagnosis of professional learners. We try to take into account the forest life to think about the impacts of human actions on the forest ecosystem with a view to sustainable development. The results presented constitute a preliminary step to the study of the benefits of a numerical environment to learn how to act in forest (Silva Numerica).